Influence of Edaphic Factors on Fusarium wilt of Bell Pepper - Attri, Kaushal; Sharma, Monica; Gupta, S. K. (International Journal of Bio-resource and Stress Management, 2018)
Fusarium wilt of bell pepper (Capsicum annuum L.) caused by Fusarium oxysporum f. sp. capsici is a damaging disease and causes huge losses to the crop. To study the effect of temperature and pH on mycelial growth of Fusarium oxysporum f. sp. capsici, an experiment was conducted under in vitro conditions. The results revealed that pathogen grew well at temperature range 15-35 °C and pH range of 4.0-9.0. However, optimum temperature for mycelial growth was recorded at 25 °C (10.65 mm day-1) followed by 30 °C (9.65 mm day-1). The most suitable pH level for growth of fungus was 7.0 (12.75 mm day-1) followed by 6.0 (10.70 mm day-1). Growth of fungus reduced drastically below 15 and above 35 °C. Similarly very low and high pH levels were not suitable for mycelial growth. To study the effect of soil temperature and soil moisture on the development of Fusarium wilt of bell pepper, an experiment was conducted in sick pots. Bell pepper seedlings were transplanted in sick pots and different soil temperature and soil moisture were maintained. It was observed that incidence of Fusarium wilt disease was maximum (100%) at soil temperature of 25 °C followed by 30 °C (75.0%) and 20 °C (37.5%) while 40% soil moisture resulted in maximum disease incidence of 66.66% followed by 50% (58.33%) and 60% (50.00%). Hence, optimum temperature for the development of Fusarium wilt of bell pepper was 25 °C whereas optimum soil moisture was 40%